2019
DOI: 10.1111/ped.13787
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric early warning score and deteriorating ward patients on high‐flow therapy

Abstract: Background Delivery of non‐invasive ventilation commonly occurs in the pediatric intensive care unit (PICU). With the advent of high‐flow nasal cannula (HFNC), patients with respiratory distress may be rescued on the ward without a PICU admission. We evaluated our ward HFNC algorithm to determine its safety profile and independent predictors for non‐responders, defined as requiring subsequent PICU admission. Methods A retrospective chart review of patients <17 years of age admitted with respiratory distress be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
(47 reference statements)
2
17
0
1
Order By: Relevance
“…Similarly, Mayordomo-Colunga et al stated the absence of RR decline at 1st and 6th hours in NIPPV failure [26]. Several models also predict HFNC failure such as RR above the 90th percentile for age at triage [1,27], no RR or HR change within sixty minutes [28] and worsening pediatric early warning scores [29]. The failure rate (13.4%) in this study was within the reported ranges of 3% and 30% [3,8,30].…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, Mayordomo-Colunga et al stated the absence of RR decline at 1st and 6th hours in NIPPV failure [26]. Several models also predict HFNC failure such as RR above the 90th percentile for age at triage [1,27], no RR or HR change within sixty minutes [28] and worsening pediatric early warning scores [29]. The failure rate (13.4%) in this study was within the reported ranges of 3% and 30% [3,8,30].…”
Section: Discussionsupporting
confidence: 77%
“…It is very important to predict the determining factors of HHHFNC therapy failure in children with RD (13,14). That will enable us to identify patients who will not respond, and thus other treatment options will not be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Although it probably has some helpful effects, there is limited evidence on using this treatment option in patients with pneumonia (8,9). There are already a few studies which evaluate the treatment success of HHHFNC for children with SBP with almost all of them being conducted in the intensive care unit (ICU) (13,14). The goal of this prospective clinical study was to determine whether the use of HHHFNC therapy is associated with a reduction in severity among children with SBP presenting to the ED.…”
Section: Introductionmentioning
confidence: 99%
“…Resource-rich settings have established that high flow is a safe, well-tolerated and feasible method for managing respiratory failure on the general paediatric ward (Mikalsen et al 2016;Sachs et al 2019). However, a cohort study from Canada reported that approximately half of children initiated on high flow in the emergency department required escalation to CPAP or BiPAP in the PICU (Hansen et al 2019). The risk of clinical deterioration after high flow initiation, the drastic difference in resource availability between resourcerich and resource-limited settings and the wide regional variability in paediatric resource availability in RLS raise the question whether high flow should be used outside the PICU in these settings.…”
Section: Applying High Flow To a Broader Patient Populationmentioning
confidence: 99%